Genome-Wide Identification of NAC Transcription Factor Family in Juglans mandshurica and Their Expression Analysis during the Fruit Development and Ripening - Xiang Li (MDPI AG, 2021)
The NAC (NAM, ATAF and CUC) gene family plays a crucial role in the transcriptional regulation of various biological processes and has been identified and characterized in multiple plant species. However, genome-wide identification of this gene family has not been implemented in Juglans mandshurica, and specific functions of these genes in the development of fruits remain unknown. In this study, we performed genome-wide identification and functional analysis of the NAC gene family during fruit development and identified a total of 114 JmNAC genes in the J. mandshurica genome. Chromosomal location analysis revealed that JmNAC genes were unevenly distributed in 16 chromosomes; the highest numbers were found in chromosomes 2 and 4. Furthermore, according to the homologues of JmNAC genes in Arabidopsis thaliana, a phylogenetic tree was constructed, and the results demonstrated 114 JmNAC genes, which were divided into eight subgroups. Four JmNAC gene pairs were identified as the result of tandem duplicates. Tissue-specific analysis of JmNAC genes during different developmental stages revealed that 39 and 25 JmNAC genes exhibited upregulation during the mature stage in walnut exocarp and embryos, indicating that they may serve key functions in fruit development. Furthermore, 12 upregulated JmNAC genes were common in fruit ripening stage in walnut exocarp and embryos, which demonstrated that these genes were positively correlated with fruit development in J. mandshurica. This study provides new insights into the regulatory functions of JmNAC genes during fruit development in J. mandshurica, thereby improving the understanding of characteristics and evolution of the JmNAC gene family.